Modified Scattering for the One-Dimensional Cubic NLS with a Repulsive Delta Potential. (8th February 2018) - Masaki, Satoshi; Murphy, Jason; Segata, Jun-Ichi
Abstract: We consider the initial-value problem for the one-dimensional cubic nonlinear Schrödinger equation with a repulsive delta potential. We prove that small initial data in a weighted Sobolev space lead to global solutions that decay in L^∞ and exhibit modified scattering.